The money problem : rethinking financial regulation - Ricks, Morgan (Chicago : The University of Chicago Press, 2016)
Years have passed since the world experienced one of the worst financial crises in history, and while countless experts have analyzed it, many central questions remain unanswered. Should money creation be considered a 'public' or 'private' activity - or both? What do we mean by, and want from, financial stability? What role should regulation play? How would we design our monetary institutions if we could start from scratch? In 'The Money Problem', Morgan Ricks addresses all of these questions and more, offering a practical yet elegant blueprint for a modernized system of money and banking.
Introduction -- Instability -- Taking the money market seriously -- Money creation and market failure -- Banking in theory and reality -- Panics and the macroeconomy -- Design alternatives -- A monetary thought experiment -- The limits of risk constraints -- Public support and subsidized finance -- The public-private partnership -- Money and sovereignty -- A more detailed blueprint -- Rethinking financial reform.
Includes bibliographical references and index.
Description based on electronic resource.
eBooks on EBSCOhost
Keywords: Bank, ...; Money market -- United States; Monetary policy -- United States; Banks and banking -- United States; Informal sector (Economics) -- United States; Financial crises -- Prevention; Marché monétaire -- États-Unis.; Politique monétaire -- États-Unis.; Banques -- États-Unis.; Secteur informel (Économie politique) -- États-Unis.; BUSINESS & ECONOMICS -- Finance; Banks and banking; Financial crises -- Prevention; Informal sector (Economics); Monetary policy; Money market; United States; Geldwirtschaft; Stabilität; Finanzkrise; Regulierung; Economics, finance, business & management; Finance; Finance and Accounting; Electronic books